The role of intention as a mediator in the relationship between self-efficacy and use of SHMS open educational resources (OER) platform in Saudi Arabia - Waleed Saud S. Alshammari; Siti Mastura Binti Baharudin; Nurul Fazzuan Khalid (Cogent Education)
The purpose of this study is to explore the relationships between self-efficacy and actual use of the Open Educational Resources (OER) Platform with mediation of intention among teachers in Saudi Arabia. Additionally, the research highlighted the importance of gender differences regarding the intention and actual use of the OER platform in the classroom. The study conducted an online survey involving 374 teachers utilizing the OER platform. The descriptive analysis using IBM SPSS 25 software and the inferential analysis using SmartPLS 4 were employed. The findings also demonstrated that self-efficacy influenced the teachers’ intentions to use the OER Platform. Furthermore, the results supported a significant and positive relationship between the intention and the teachers’ utilization of the OER platform. Meanwhile, the results showed that self-efficacy had a significant indirect on the actual use of the OER platform through mediating of intention. Moreover, based on the findings, it can be inferred that there are no discernible variations in intentions, self-efficacy, and platform usage based on gender, aligning with the findings across different educational and entrepreneurial settings. By understanding and addressing these factors, educational institutions can better support teachers in effectively integrating the OER Platform into their instructional practices.